Bentuk Penyajian Tari Jepin Laba-Laba di Desa Penibung Kecamatan Mempawah Hilir Kabupaten Mempawah - Ramadhan Kasyful Kalam; Dwi Oktariani; Mega Cantik Purti Aditya (SENDRATASIK UNP, 2023)
This research aims to describe and document the presentation of the Jepin Spider Dance. The researcher's interest was motivated by knowing the dance performance from start to finish. This research uses descriptive methods, qualitative research forms, and a choreographic approach. The data collection techniques used are observation, interviews and documentation techniques. The technique for testing the validity of the data used is extended observation and source triangulation. Based on data analysis, it can be concluded that the form of presentation of the Jepin Spider Dance, the Jepin Spider Dance is an entertainment dance that is performed at Khataman qur'an, circumcision, wedding and robo-robo events. The movement motif in the Jepin Spider Dance uses a single-step movement motif. There are two types of movement, namely the one-go type and the two-return type. This style is divided into initial, middle and final movements. This variety forms a connective pattern resembling a spider's nest. Each change of movement is marked by a tahto or tahtim movement. The Jepin Spider Dance Costume uses a clothes bracket and a telok belanga. Using realistic make-up from the dancer's real face. The musical accompaniment to the Jepin Spider Dance instrument uses Arabic poetry, meaning praise to the Prophet Muhammad. The instruments use the Gambus or Selodang and Beruas musical instruments. This dance uses rope properties which are played by nine dancers.